A comparison of Low Dose with Standard Dose Chest CT Scan in Diagnosis of COVID-19 - Mughal, Hina Hanif; Imran Aftab, Muhammad; Ali, Madiha; Mehmood, Faisal; Yaqoob, Sana; Majeed, Mutayyaba (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: Comparison of safety profile of low dose CT scan chest with standard dose CT scan in Covid 19. Study design: Prospective study Place and duration of study: Department of Radiology, Benazir Bhutto Hospital, Rawalpindi from -01-09-2020 to 31-03-2021. Methods After approval from ERB, 45 COVID-19 positive patients diagnosed by PCR, aged 55 years and above were selected. In the prospective study, these patients with normal CXR were advised for same day chest CT scan. Initially, a standard dose of chest CT scan of 150mAs was applied. After assessing the chest signs of Covid on scan, a low-dose CT of 30mAs was performed instantly. A comparison was made to check the diagnostic accuracy of standard-dose and low-dose CT for the identification of features of typical COVID19 pneumonia. Results: The mean age of patients was 58.27±7.23. An admirable intra-reader agreement was found between low- and standard-dose CT in identifying typical findings of COVID pneumonia (intraclass correlation coefficient [ICC] = 0.98–0.99 with A p value of less than 0.001 of all readers). Mean effective dose values of low and standard dose groups were 1.69±0.38 mSv and 7.21±1.23, correspondingly. Values of absolute cancer risk per mean cumulative effective dose of low & standard dose chest CT examinations were 0.68 × 10−4 and 2.41×10−4 respectively. Conclusions: The low dose CT chest protocol is better than standard dose for the identification of typical COVID-19 pneumonia features in routine practice with substantial decrease in dose of radiation as well as estimated cancer risk.